Analysis of Lexical and Grammatical Cohesion in Short Stories Nasi Aking untuk Calon Presiden by Manaf Maulana as a Discourse Learning Media - Puji Anto; Fauzi Rahman; Sahrul Umami (Universitas Indraprasta PGRI, 2021)
Cohesion is very important in a discourse to combine sentences and between sentences. One of the elements that can be used as a measure of a discourse is cohesive or cannot be seen from the use of cohesion. The short story entitled Nasi Aking for Presidential Candidates by Manaf Maulana was chosen as the object of research because the text uses a lot of cohesion markers, both lexical and grammatical, so it is necessary to identify what types of cohesion exist. The results of the research will be used as a medium for learning discourse. The approach used in this research is a qualitative descriptive approach. The data source used is a short story with the title Nasi Aking for Presidential Candidates by Manaf Maulana. The research data are discourse texts which allegedly apply a certain type of cohesion. The technique used to collect data is the listening and note-taking technique. Data analysis in this study used the agih method. The results of this study show that there are several types of cohesion, such as lexical cohesion including reiteration and collocation, while grammatical cohesion includes conjunctions, substitutions, ellipsis, and references. Based on the description of the recapitulation table of the analysis of the entire paragraph, the most data that has been found from 25 sentence pairs in the short story